High-Throughput 3D In Vitro Tumor Vasculature Model for Real-Time Monitoring of Immune Cell Infiltration and Cytotoxicity - Song, Jiyoung; Choi, Hyeri; Koh, Seung Kwon; Park, Dohyun; Yu, James; Kang, Habin; Kim, Youngtaek; Cho, Duck; Jeon, Noo Li (Frontiers in Immunology, 2021)
Recent advances in anticancer therapy have shown dramatic improvements in clinical outcomes, and adoptive cell therapy has emerged as a type of immunotherapy that can modulate immune responses by transferring engineered immune cells. However, a small percentage of responders and their toxicity remain as challenges. Three-dimensional (3D) in vitro models of the tumor microenvironment (TME) have the potential to provide a platform for assessing and predicting responses to therapy. This paper describes an in vitro 3D tumor model that incorporates clusters of colorectal cancer (CRC) cells around perfusable vascular networks to validate immune cell-mediated cytotoxicity against cancer cells. The platform is based on an injection-molded 3D co-culture model and composed of 28 microwells where separate identical vascularized cancer models can be formed. It allows robust hydrogel patterning for 3D culture that enables high-throughput experimentation. The uniformity of the devices resulted in reproducible experiments that allowed 10x more experiments to be performed when compared to conventional PDMS-based microfluidic devices. To demonstrate its capability, primary natural killer (NK) cells were introduced into the vascularized tumor network, and their activities were monitored using live-cell imaging. Extravasation, migration, and cytotoxic activity against 6 types of CRC cell lines were tested and compared. The consensus molecular subtypes (CMS) of CRC with distinct immune responses resulted in the highest NK cell cytotoxicity against CMS1 cancer cells. These results show the potential of our vascularized tumor model for understanding various steps involved in the immune response for the assessment of adoptive cell therapy.